PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN - Neneng Sri Suprihatin; Arinda Ayu Ananthy (Jurnal Riset Akuntansi Terpadu, 2019)
This study aims to look at the effect of applying government accounting standards to the quality of financial statements and the influence of accounting information systems on the quality of financial statements. By using the population of all sub-districts in the Serang city government using a questionnaire at the leadership and financial management staff at the district level. The data processing method uses Partial Least Square (PLS) software as a differentiator from previous research. The results showed that there was a positive and significant effect between the SAP implementation variables on the quality of financial statements as indicated by the original sample estimate value of 0.421 and t-statistics of 3.567 (greater than t-table, ± 2.750). Whereas the relationship between SIA and the quality of financial statements based on data processing obtained, has a positive and significant relationship as indicated by the original sample estimate value of 0.644 and t-statistics of 6.315 (greater than t-table, ± 2.750).